The Squamous Vaginal Papillomatosis in Prepubertal Female Twins: A Case Report - Boreikaitė, Evelina; Bilius, Vytautas; Bumbul-Mazurek, Elžbieta; Bumbulienė, Žana (Acta medica Lituanica, 2021)
This is the first case describing vaginal papillomatosis with a fibroepithelial polyp of the vulva in a prepubertal girl and vaginal papillomatosis in her twin sister. Parents contacted pediatric urologist regarding their eight-year-old daughter (twin A), who had a growth next to the external urethral meatus. The girl was referred to a pediatric surgeon. The exophytic 3 cm long structure with necrosis on top was found. After obtaining informed consent from girl parents, pediatric surgeon removed the exophytic structure and perform cystoscopy and vaginoscopy for possible changes in the bladder and vagina. Cystoscopy findings were normal. On vaginoscopy, numerous macroscopic papillomatous structures were identified on the cervix and vaginal walls. Vaginal biopsies were performed on the areas affected by papillomatosis. Histopathologic examination showed a fibroepithelial polyp with a central fibrovascular core covered by squamous epithelium and vaginal squamous papillomatosis. The decision was made to perform vaginoscopy on her twin sister (twin B), too. On vaginoscopy, solitary small vaginal papillomas were also found. In this case manifestation of vaginal papillomatosis in twins might have been influenced by inheritance and the same bacterial and viral environment.